Safety of topical interventions for the treatment of actinic keratosis - Koch, Elias; Wessely, Anja; Steeb, Theresa; Berking, Carola; Heppt, Markus (Expert Opinion on Drug Safety, 2021)
Introduction: Actinic keratosis (AK) are proliferations of atypical keratinocytes that may eventually progress to cutaneous squamous cell carcinoma. Therefore, AK requires consequent and early treatment. Areas covered: A variety of effective approaches is currently available for the clearance of AK. These interventions may be applied either in a lesion-directed or field-directed mode as AK can occur as single or multiple lesions. Field-directed approaches typically comprise topical drug-mediated interventions which aim at eliminating all visible lesions and also at clearing subclinical changes of the actinically damaged field. However, most treatment options are associated with local adverse events such as erythema, scaling, pain, and rarely with systemic symptoms. This expert review provides a comprehensive and up-to-date overview of the safety considerations of the commonly prescribed topical treatment agents cyclooxygenase inhibitors, 5-fluorouracil, imiquimod, ingenol mebutate, and photodynamic therapy. All these therapies have been proven efficient, yet they differ considerably regarding their safety profile. Expert opinion: In the future, safety concerns will relate to long-term and irreversible adverse drug events instead of application site reactions. In particular, the rate of treatment-associated non-melanoma skin cancers will increasingly come into focus and warrant investigation in postmarketing surveillance trials with a long-term follow-up.
CRIS-Team Scopus Importer:2021-08-06
Keywords: 5-fluorouracil; actinic keratosis; diclofenac; imiquimod; ingenol mebutate; photodynamic therapy